11.3k views
4 votes
How do I find the answer to this math equation?

How do I find the answer to this math equation?-example-1
User GPW
by
4.8k points

1 Answer

3 votes

The given equation is expressed as

- (2x + 4) = 3x - 5

The first step is to open the bracket on the left habd side of the equation by multiplying each term inside the bracket by - 1 which is outside the bracket. Thus, we have

- 1 * 2x + - 1 * 4 = 3x - 5

- 2x - 4 = 3x - 5

Collecting liketerms, we have

- 2x - 3x = - 5 + 4

- 5x = - 1

Dividing both sides of the equation by - 5, it becomes

- 5x/- 5 = - 1/- 5

x = 1/5

User Stereoputrid
by
4.8k points